Short Communication: Histopathology of red chilli fruit (Capsicum annuum) infected with Colletotrichum acutatum of Java, Indonesia isolates - Junisafitri Muljowati; Loekas Soesanto; Laurentius Nugroho (Society for Indonesian Biodiversity, 2021)
Abstract. Muljowati JS, Soesanto L, Nugroho LH. 2021. Short Communication: Histopathology of red chilli fruit (Capsicum annuum) infected with Colletotrichum acutatum of Java, Indonesia isolates. Biodiversitas 22: 874-880. Colletotrichum acutatum isolates from Malang, Temanggung, Kulonprogo, Brebes, Garut, and Pandeglang in Indonesia varied in their ability to produce pigments. In the present study, the histopathological status of red chilli was investigated during the early phase of infection by C. acutatum Java isolate. The results included a description of the histopathological features of red chillies (Capsicum annuum) in the early phase of infection by C. acutatum isolates and the relationship between the origin of the isolates and the time of onset of infection. The red chilli fruits were inoculated with fungal conidia suspension and then the histopathology of chilli fruits was observed at 0 hours (uninfected control), 8 hours, 16 hours, 24 hours, and 32 hours after inoculation. The results showed that C. acutatum isolates from Kulonprogo caused host damage within 8 hours, while the other isolates (from Malang, Brebes, Garut and Pandeglang) began to produce similar symptoms at 16 hours or 24 hours. This study revealed for the first time that pathogenic activity begins at the onset of infection, and the resulting anatomical damage to red chillies begins at different times.